The Association of Exchange Rate, Foreign Debt and Bankruptcy Risk On Hedging Decisions During the Pandemic - Aulia Ramadina Salsabila; Widya Rizki Eka Putri; Ratna Septiyanti; Sari Indah Oktanti Sembiring (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
This study aims to provide empirical evidence on the association between exchange rates, foreign debt, and bankruptcy risk on hedging decisions during a pandemic. The subjects of this research are Conventional General Banking companies registered with the Financial Services Authority (OJK) in 2020 and 2021. The hypotheses are tested using multiple linear regression analysis. Hedging is measured using the value of derivative instruments reported in the banks' financial statements. The test results in th is study indicate that the exchange rate proxies by the mid-rate at the closing price of the rupiah exchange rate against the US dollar has no relationship with hedging decisions because the exchange rate fluctuations during the pandemic are still within reasonable limits according to the assumptions of the Ministry of Finance. Meanwhile, the results of the test of foreign debt measured by the ratio of foreign currency debt to total debt and bankruptcy risk measured by the Altman Z- score model have a relationship with hedging decisions because hedging decisions will be important to reduce the risk of changes in the value of foreign debt, and firms experiencing bankruptcy risk will implement hedging strategies to mitigate financial risk and protect the firm from significant losses.